Dynamic simulation of transformers / Azirin Sulaiman Rasul - Sulaiman Rasul, Azirin (2002)
This project is about dynamic simulation of transformers' various connections using a simulation software program. It covers modelling of transformer and simulating its different types of connections namely two-winding transformer, auto transformers and three-phase transformer. Simulation and testing at different operating conditions for single-phase two-winding transformer such as short-circuit, open-circuit, RL and RC load terminations, in-rash current, dc-bias core saturation, and transformer load tests with the inclusion of core saturation are developed and performed. Ratio tests for auto transformers and three-phase transformer are also included in the simulations. Simulation and analysis of zero-sequence current components during balance and unbalance conditions for Delta-Wye three-phase transformer are included in the scope of this project.